In situ fluorescence activation of DNA–silver nanoclusters as a label-free and general strategy for cell nucleus imaging. Issue 9 (12th January 2018) - Li, Duo; Qiao, Zhenzhen; Yu, Yanru; Tang, Jinlu; He, Xiaoxiao; Shi, Hui; Ye, Xiaosheng; Lei, Yanli; Wang, Kemin
Abstract : A simple, specific, label-free and general nucleus imaging strategy was developed based on in situ fluorescence activation of silver nanoclusters. Abstract : A facile, general and turn-on nucleus imaging strategy was first developed based on in situ fluorescence activation of C-rich dark silver nanoclusters by G-rich telomeres. After a simple incubation without washing, nanoclusters could selectively stain the nucleus with intense red luminescence, which was confirmed using fixed/living cells and several cell lines.